Developing the Experience Impact Scale: A qualitative study using a study abroad and international internship program. (15th March 2022) - Lundberg, Neil; Ward, Peter; Lundberg, Grant; Hill, Brian; Bown, Jennifer; Zabriskie, Ramon; Duerden, Mat; Ashby, Heather
Abstract: Recent work has identified different experience types, including experience classifications of ordinary, memorable, meaningful, and transformative. This study further clarifies the experience typology through qualitative data analysis of each experience type. Data analysis identified that within each extraordinary experience type, additional subtypes were present. Experience types and subtypes were organized according to the experience typology continuum into a 10-item Experience Impact Scale (EIS), as no instrument to measure experience types or experience impact was available. An expert panel was used to determine the representativeness of the items in the EIS and to provide content-related evidence of validity. Discussion of the findings and future recommendations regarding the scale are provided.